2021
DOI: 10.3390/ijms221910649
|View full text |Cite
|
Sign up to set email alerts
|

Novel P2X7 Antagonist Ameliorates the Early Phase of ALS Disease and Decreases Inflammation and Autophagy in SOD1-G93A Mouse Model

Abstract: Amyotrophic lateral sclerosis (ALS) is a disease with a resilient neuroinflammatory component caused by activated microglia and infiltrated immune cells. How to successfully balance neuroprotective versus neurotoxic actions through the use of anti-inflammatory agents is still under debate. There has been a boost of awareness regarding the role of extracellular ATP and purinergic receptors in modulating the physiological and pathological mechanisms in the nervous system. Particularly in ALS, it is known that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…At a terminal stage, antagonist-treated mice displayed a significant reduction in pro-inflammatory cytokines and autophagy markers compared to vehicle controls. Surprisingly, AXX71 did not affect anti-inflammatory markers, motor neuron survival, or overall lifespan …”
Section: P2x7 Receptor Antagonists In Mouse Models Of Alsmentioning
confidence: 90%
See 2 more Smart Citations
“…At a terminal stage, antagonist-treated mice displayed a significant reduction in pro-inflammatory cytokines and autophagy markers compared to vehicle controls. Surprisingly, AXX71 did not affect anti-inflammatory markers, motor neuron survival, or overall lifespan …”
Section: P2x7 Receptor Antagonists In Mouse Models Of Alsmentioning
confidence: 90%
“…These effects could be ameliorated by the use of antagonist A-804598 . Similarly, a recent in vivo study of SOD1 G93A mice found that novel P2X 7 R antagonist AXX71 successfully ameliorated autophagy …”
Section: Role Of the P2x7 Receptor In Amyotrophic Lateral Sclerosismentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, increased ATP levels in ALS patients CSF were measured [ 129 ]. Importantly, Apolloni et al demonstrated that the antagonism of P2X7 receptor in a SOD1-G93A mouse model of ALS ameliorates the early symptomatic phase of the disease by reducing microglia-related pro-inflammatory markers and autophagy [ 130 ]. In fact, the activation of P2X7 receptor in SOD1-G93A mouse leads to the increase in autophagic flux in microglia [ 131 ] and increased oxidative stress [ 132 ] concomitantly with the enhancement of pro-inflammatory action of microglia [ 133 ].…”
Section: Damage-associated Molecular Patterns Released From Mitochond...mentioning
confidence: 99%
“…On the other hand, increased ATP levels in ALS patients CSF were measured [125]. Importantly, Apolloni et al demonstrated that the antagonism of P2X7 receptor in a SOD1-G93A mouse model of ALS ameliorates the early symptomatic phase of the disease by reducing microglia-related pro-inflammatory markers and autophagy [126]. In fact, the activation of P2X7 receptor in SOD1-G93A mouse leads to the increase of autophagic flux in microglia [127] and increased oxidative stress [128] concomitantly with the enhancement of pro-inflammatory action of microglia [129].…”
Section: Atpmentioning
confidence: 99%